THE EFFECT OF THE NUTRITION PROBLEM TODDLER ASSISTANCE PROGRAM IN THE DUKUH KUPANG HEALTH CENTER AREA, SURABAYA CITY - Ulya, Aura Syafiroh; Elvandari, Millyantri (HEARTY, 2025)
Toddlers are the age when children experience optimal growth and development. The period of growth and development at this age is a period that occurs quickly and never repeats itself, so that the growth and development period in young children is often called the golden age. One form of support for toddler nutrition concerns, the Surabaya City Health Office initiated a flagship program related to toddler nutrition problems in Surabaya City, one of which is the toddler nutrition assistance program as an effort to support accelerated improvement in nutritional status in toddlers can be achieved immediately and prevent the occurrence of stunting toddlers in Surabaya City. The study aims to see how the impact of the toddler nutrition assistance program at Puskesmas Dukuh Kupang. The type of research is quantitative, namely by measuring the increase/comparison of eating patterns and nutritional status before and after the nutrition assistance program. The population in this study were all underweight toddlers in the Puskesmas Working Area. Dukuh Kupang as many as 26 people. The sample is all mothers who have undernourished toddlers in the Dukuh Kupang Health Center Working Area as many as 26 people using sampling techniques, namely total sampling. Data collection using observation sheets and interviews. Univariate data analysis using frequency distribution, bivariate analysis using Wilcoxon match paired test and multivariate analysis using logistic regression. The results of the logistic regression test obtained the value of Exp (B) in the logistic regression analysis of eating parenting has a value of 85.008 which means that eating parenting has a chance of 85.008 times to change. While the nutritional status variable has an Exp (B) value of 3.663, from these results it can be explained that nutritional status has an increased chance of 3.663 times.